Praktik Evaluasi Program Pendidikan: Pendekatan Komprehensif untuk Peningkatan Kualitas - Anwar Hidayat; Dwi Rahayu; Deti Elice; Sovia Mas Ayu (Kartika: Jurnal Studi Keislaman, 2026)
Educational program evaluation is a systematic process that is essential in improving learning quality and achieving educational institutional objectives. This research aims to examine the practice of educational program evaluation with focus on basic concepts, evaluation models, principles of implementation, and their application in the context of modern educational institutions. The research method employs a library research approach with in-depth analysis of various recent academic literature from 2015-2025 that discusses educational program evaluation, the CIPP model (Context, Input, Process, Product), and strategies for improving educational quality. The research findings indicate that effective educational program evaluation must be guided by principles of comprehensiveness, continuity, objectivity, and sustainability. The CIPP model has proven to be effective as a comprehensive evaluation framework at every stage of the program. Implementation of evaluation requires systematic stages that include preparation, implementation, and follow-up, as well as support from adequate policies and resources. The implication of this research is that educational institutions need to integrate program evaluation as an integral part of the quality management system to ensure the relevance and effectiveness of programs in meeting the needs of students and society.